Recognition of piano notes with the aid of FRM filters - Foo, Say Wei (2009)
An approach to recognition of piano notes using the Analysis-by-Synthesis technique is described in this paper. It is assumed that several notes may be played simultaneously and only a single signal source is available. The analysis is carried out in the frequency domain using Constant-Q Transform. In cases where the harmonics of notes are very close to one another, Frequency Response Masking (FRM) filters with suitably chosen selectivity and bandwidth are used to resolve the ambiguity. The method was tested with recording from an acoustic piano played by professional pianists. Results show that the system is able to resolve up to six simultaneous notes with high accuracy.